Predicting the characteristics of a C2B6 monolayer with ultrahigh carrier mobility - Xu, Ping; Zhu, Zhengyang; Zheng, Ruxin; Sun, Qingyun; Ma, Zhen; Mu, Weihua; Cui, Zhen (Frontiers in Chemistry, 2024)
Two-dimensional materials have excellent electronic and optical properties suggesting absolute advantages in the application of nanodevices. In this work, new two-dimensional material (C2B6 monolayer) is proposed with puckered structure and also presents dynamic and thermal stability calculated by first principles simulations. Interestingly, the C2B6 monolayer possesses semiconductor behavior with ultranarrow bandgap only about 0.671 eV by HSE06 functional. While the hole in the C2B6 monolayer shows ultrahigh mobility as about 6342 cm 2 •V -1 •s -1 in decent transport directions, which is larger than traditional transition metal dichalcogenides materials. More importantly, the pronounced anisotropy of mobility of the electrons and holes can separate the photogenerated charges, suggesting the C2B6 monolayer as excellent photocatalyst. Then, the novel properties of the light absorption characteristic are obtained and the anisotropic photocurrent also imply the C2B6 monolayer can be used as a potential photoelectric device. Our results provide theoretical guidance for the design and application of two-dimensional materials.